2007
DOI: 10.1111/j.1467-9280.2007.01905.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsaccades and Attention: Does a Weak Correlation Make an Index?

Abstract: In the recent literature on microsaccades and attention, two questions have been conflated. There is a broad question of whether microsaccades are related to attention, and there is a more specific question about whether microsaccades serve as an index of attention. We are happy to agree that microsaccades are related to attention. However, the claim that ''microsaccades are an index of covert attention'' (in the title of Laubrock, Engbert, Rolfs, & Kliegl, 2007, this issue) depends on a strong correlation. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 2 publications
(6 reference statements)
0
13
0
Order By: Relevance
“…Although there is some debate concerning the suitability of microsaccades as an index of attention (Horowitz, Fencsik, Fine, Yurgenson, & Wolfe, 2007; Horowitz, Fine, Fencsik, Yurgenson, & Wolfe, 2007; Laubrock, Engbert, Rolfs, & Kliegl, 2007), we found that making a microsaccade significantly affected the subject’s behavioral performance, suggesting that in this case, microsaccades can indeed reveal the locus of covert spatial attention. Similar to the findings in humans, we found that focusing attention on an item significantly affects the representational precision of memories.…”
Section: Discussionmentioning
confidence: 69%
“…Although there is some debate concerning the suitability of microsaccades as an index of attention (Horowitz, Fencsik, Fine, Yurgenson, & Wolfe, 2007; Horowitz, Fine, Fencsik, Yurgenson, & Wolfe, 2007; Laubrock, Engbert, Rolfs, & Kliegl, 2007), we found that making a microsaccade significantly affected the subject’s behavioral performance, suggesting that in this case, microsaccades can indeed reveal the locus of covert spatial attention. Similar to the findings in humans, we found that focusing attention on an item significantly affects the representational precision of memories.…”
Section: Discussionmentioning
confidence: 69%
“…The cause of this microsaccade direction effect has been controversial. While there have been multiple suggestions that microsaccades can serve as an overt indicator of covert spatial attention [6][7][8]13,14,[18][19][20][21] , others propose a dependency on other factors, such as complicated oculomotor response to visual stimuli [22][23][24][25][26][27][28] .…”
Section: Discussionmentioning
confidence: 99%
“…Barlow (1952) proposed that microsaccades occur upon a shift of visual attention, and it has since been shown that microsaccade rate is indeed modulated by shifts of attention (Engbert and Kliegl, 2003; Hafed and Clark, 2002; Horwitz and Albright, 2003; Rolfs et al, 2004; Tse et al, 2002, 2004; Turatto et al, 2007; Valsecchi and Turatto, 2009) and perceptual state (Hsieh and Tse, 2009; Martinez-Conde et al, 2006), although microsaccade occurrence is not limited to the time of attentional shifts or perceptual shifts (Tse, Caplovitz and Hsieh, 2009). However, there has been a debate about whether microsaccade directionality is also influenced by the directionality of attentional shifts, with some arguing for an influence of attention (Engbert, 2006; Engbert and Kliegl, 2003; Hafed and Clark, 2002; Laubrock et al, 2007; Rolfs et al, 2004; Turatto et al, 2007; Valsecchi and Turatto, 2009), and others finding that attention plays no significant role in the distribution of microsaccade directions (Horwitz and Albright, 2003; Horowitz et al, 2007a, b, Tse et al, 2002, 2004). Whether microsaccade directionality is correlated with attentional directionality or not, the fact that microsaccade rate is modulated by attentional shifts suggests that eye-shifting circuitry is not independent of attention-shifting circuitry.…”
Section: Discussionmentioning
confidence: 99%